Effect of Foreign & Domestic Investment on Manufacturing Industry Performance and Its Impact on Unemployment and Poverty (Case Study in Tangerang City) - Purno, Marhaendro; Supriyanto, Supriyanto; Jayanti, Indah; C.K, Dwi Ferdiyatmoko; Irawan, Seri; Singgih, Eman; Mendrofa, Yeremia (PT FORMOSA CENDEKIA GLOBAL, 2024)
FDI is very important in driving the economies of emerging market countries through free trade, banking, production, and other sectors, which ultimately leads to better growth. Therefore, it is believed that access to FDI can resolve economic and social issues. For example, FDI enhances the labor market and helps reduce unemployment rates in the concerned country.This research uses a qualitative approach. According to Denzin & Lincoln in) and Jane Richie, research utilizes concepts, behaviors, perceptions, and issues to present the social world and the perspectives of the individuals being studied. This method aligns with the term “qualitative research,” which means that this research is integrated with qualitative research. From 2010 to 2023, investment growth in Indonesia’’s manufacturing industry has gradually declined. The purpose, according to the Law of the Republic of Indonesia number 25 of 2007 concerning investment, is to create job opportunities for the community. In articles 10 and 13 of the law, paragraph 1 states that investment companies must prioritize Indonesian citizens for labor needs, and article 13 paragraph 2 states that the government is responsible for fostering and developing micro-enterprises. Based on the results and analysis of the research conducted, the author concludes that during the research period from 2010 to 2023, the city of Tangerang, which is the largest city in Banten Province, has made efforts to attract both domestic and foreign investors. Foreign investors come from several countries such as Malaysia, South Korea, England, Singapore, and Taiwan.